(untitled) (Annals of Medical Research, 2021)
Aim: The goal of the present study was to evaluate the effect of birth weight percentile on adverse neonatal morbidity in term uncomplicated pregnancies.Material and Methods: This retrospective analysis comprised 7,817 pregnant women with uncomplicated pregnancies and single deliveries at term. The babies were divided into groups according to birth weight percentiles as follows: (1) Small for gestational age (SGA) (10 percentile), (2) 10–25 percentile, and 26–90 percentile. The primary outcome was adverse neonatal morbidity (ANM), defined as any of the following: Apgar score 4 at 5 min; respiratory distress; mechanical ventilation; intraventricular hemorrhage, grade III or IV; necrotizing enterocolitis, stage 2 or 3; neonatal sepsis, stillbirth or neonatal death.Results: Demographic and obstetric characteristics of the mothers were similar among the groups. ANM rates were 10.7% in the SGA group, 6.8% in the 10–25 percentile group, and 2.1% in the 26–90 percentile group, a significant difference. ANM was 5-fold higher in the SGA group and 3.2-fold higher in the 10–25 percentile group than in the 26–90 percentile group. Delivery induction or augmentation, cesarean delivery for non-reassuring fetal heart rate or fetal distress, Apgar score 4 at 5 min, mechanical ventilation, neonatal sepsis, stillbirth, or neonatal death significantly increased in the 10–25 percentile group compared with those in the 26–90 percentile group. Conclusion: The present study indicated that in uncomplicated pregnancies, fetuses with birth weights within the 10–25 percentile had a significantly increased risk of ANM compared to those within the 26–90 percentile.